Sejarah Pembaharuan Hukum Keluarga di Negara Islam - Pertiwi, Endah Mustika; Syarifuddin; Murtadho Emzaed, Ali (TERAJU: Jurnal Syariah dan Hukum, 2025)
Family law has a central role in the study of Islamic law because it is considered the starting point for understanding Islamic law. In the mid-20th century, reform and renewal occurred. This research aims to describe the history of family law that occurred in Islamic countries using normative research methods. Data collected through relevant document sources related to the history of family law. The results of this study are as follows: 1) Islamic countries are defined as countries that apply Islamic law purely and countries with the largest adherents of Islam; 2) Family law reform is divided into two categories: intra-doctrinal reform and extra-doctrinal reform; 3) Family law reform began in Turkey in the early 20th century, followed by Egypt, Iran, Syria, Pakistan and Indonesia.